Retardo en Redes Inalámbricas Colaborativas - Hernández-Suárez, Cesar Augusto; Giral-Ramírez, Diego Armando; Pedraza-Martínez, Luis Fernando (Revista Científica, 2020)
Cognitive radio is a technology that makes efficient use of the spectrum allowing secondary users to use the spectral opportunities of the licensed bands, but without interfering with the communications of the primary users. The objective of this article is to analyze and compare the performance of two multicriteria decision making algorithms: Topsis and Vikor, with different levels of collaboration between secondary users. The two algorithms are evaluated and compared at the delay level during an information transmission of 9 MB. The comparison is made under four different scenarios, according to the class of service and the level of traffic, for the GSM frequency band. According to the results achieved, the Topsis algorithm has a better performance in different scenarios and collaboration levels.